Paternal biopsychosocial resilience in triadic interactions among African American/Black families exposed to trauma and socioeconomic adversity. Issue 6 (27th July 2021) - Bocknek, Erika London; Lozada, Fantasy T.; Richardson, Patricia; Brown, Deon; McGoron, Lucy; Rajagopalan, Adithi
Abstract: Fathers have a distinct and unique effect on child development, but little is known about fathering beyond White or majority White families. The current study includes African American/Black biological fathers ( N  = 88) and their two‐year‐old children. Fathers reported low incomes and high rates of depression and posttraumatic stress disorder (PTSD). Parenting behaviors were observed in high‐stress and low‐stress triadic contexts. In the high‐stress condition,  we assessed paternal responses to children's bids after the family was reunited following a separation paradigm. In the low‐stress condition, we assessed parenting behaviors during a teaching task. Fathers' social baseline respiratory sinus arrhythmia (RSA) was obtained as an index of parasympathetic arousal. RSA moderated the association between PTSD and fathers' responsiveness ( F  = 6.90, p  = .00, R 2  = .30), with no association between PTSD and responsiveness demonstrated among fathers with the highest levels of RSA relative to the sample (effect = .04, p  = .00; CI [0.02, 0.06]). RSA did not moderate the association between paternal depression and parenting behaviors ( p  > .05). Furthermore, responsiveness was only significantly associated with low‐stress paternal teaching behaviors for fathers with lower RSA ( F  = 4.34, p  = .01, R 2  = .21; effect = –.19, p  = .00; CI [0.06, 0.32]). Findings demonstrate significant relationships among RSA, PTSD, and parenting for African American/Black men in contexts of economic adversity.